Discourse on Justice in the Era of Digital Determinism: A Critical Analysis of Legal Certainty and Business Risk in the Implementation of Indonesia's Core Tax System - Bahori Ahoen (Green Publisher Indonesia, 2025)
Global public administration is currently gripped by a techno-solutionism narrative, in which digitalization is seen as a panacea for bureaucratic inefficiency. This article presents a critical analysis of one of the most ambitious manifestations of this narrative in a developing country: Indonesia's Core Tax Administration System (PSIAP). Through the lens of critical legal theory and procedural justice, we centrally argue that the top-down, technology-driven implementation of PSIAP creates a juridical dissonance—a fundamental friction between the deterministic logic of algorithmic efficiency and the dialogic, certainty-based principles of business law. Using a juridical-empirical approach, this research unpacks how this dissonance manifests in three critical arenas: (1) the diffusion of accountability within an integrated data ecosystem that obscures legal accountability; (2) the erosion of due process through automated,